P1014The natural history of atrial fibrillation after the first clinical episode: a prospective observational study via implantable loop recorders. (18th June 2020) - Papakonstantinou, P; Simantirakis, E; Kanoupakis, E; Parthenakis, F; Vardas, P
Abstract: Funding Acknowledgements: The study was supported by Medtronic Inc Background The natural history of paroxysmal atrial fibrillation (AF) after the first clinical AF episode is not well known. AF burden is of clinical significance as it may have clinical implications concerning the long-term management of the arrhythmia and the decision-making on AF patients. Purpose To observe the natural history of AF in patients after their first clinical paroxysmal AF episode. Methods Thirty consecutive patients (age 66.9 ± 10 years; 14 men) received an implantable loop recorder (ILR) after their first symptomatic paroxysmal AF episode. We recorded the AF recurrences and burden (clinical and subclinical AF) during a follow-up period of three years. We excluded patients with persistent or permanent AF and patients with an episode of AF attributed to reversible or transient causes. Results Eight patients (26.6%) did not present any AF recurrence during the first year of the follow-up period. Five patients (16.6%) did not also suffer any AF episode during the second year, while in three patients (10%) no AF episode was recorded during the three-year follow-up period. In 16 patients (53.3%) the AF burden was increased during the second year of follow-up period while in 9 patients (30%) the AF burden was decreased. During the third year of follow-up period the AF burden was increased in 19 patients (63.3%), decreased in 7 patients (23.3%) and remained almost the same in 4 patients (13.3%). Five patients (16.6%) presented at least one episode of persistent AF during the follow-up period. Seven patients (23.3%) suffered only from symptomatic AF episodes, while in nine patients (30%) only asymptomatic AF episodes were recorded. Eleven patients (36.7%) had both types of AF episodes (symptomatic and asymptomatic). Conclusions The AF recurrence and burden increased in most AF patients during the three-year follow-up period. However, some patients did not suffer any AF recurrence or they presented a decrease in AF burden. Paroxysmal AF clinical profile differs among the AF patients significantly and this indicates that an individualized approach via long-term rhythm monitoring may be of clinical significance, at least in some newly diagnosed AF patients.